Simulating the Impact of Compact City Policy on Two Korean Cities: Daejeon and Hwaseong - Donghan Kim; Haejin Han (European Regional Science Association (ERSA), 2015)
The notion of compact city has become an important planning agenda to achieve a sustainable urban future. Although there is no universally accepted definition of a compact city, in terms of land use, the concept generally focuses on high-density and mixed-use development along with the promotion of public transport. It is then generally agreed that such urban development practices would yield various economic, environmental, and social benefits. To understand the impact of the compact city better, we need to develop and use relevant scientific policy support tools. Spatially explicit urban models hold some answers because they yield a logical framework for understanding complex urban systems and provide a virtual laboratory for investigating the outcomes of various urban policy actions. Whereas some urban models are developed for a specific purpose or region, some are developed as generic models to answer general urban policy questions across different cities and regions. The main goal of this research is to suggest ways of using and developing urban models in order to study compact city systems with empirical case studies. We conducted two separate but related urban simulations, first applying a generic urban model to Hwaseong, Korea. There is a wide range of generic urban models, but many of them are proprietary and require a comprehensive input data set to run the model. Thus, the usability of many generic urban models is limited, and in this research, we attempt to use a non-proprietary urban model with fewer data requirements than most. The SLEUTH model fits this purpose well. Although the model is not designed to study the impact of the compact city itself, it is one of the most widely used urban growth simulation models capable of offering some implications for the study of the compact city. Second, it develops an experimental but dedicated urban simulation model for the compact city system. Because developing a comprehensive model for the compact city requires long-term, large-scale research and development, we attempted to develop a pilot model focusing on the impact of compact city policy on urban growth. Then, we drew implications for the further development of a °compact city model.±
Keywords: R; 330; agent based model; cellular automata model; urban growth